Geometrical Optimization and Thermal-Stability Characterization of Te-Free Thermoelectric Modules Based on MgAgSb/Mg3(Bi,Sb)2 - Ying, Pingjun; Reith, Heiko; Nielsch, Kornelius; He, Ran (Small, 2022)
Solid-state thermoelectric (TE) technology is a promising approach to harvest low-grade waste heat (<573 K) and converts it to useful electricity in industrial and civilian settings. After decades of efforts in improving the figure-of-merit (zT) of TE materials, the development of advanced modules has started springing up in recent years. Although high-performance modules have been largely reported based on the successful material improvement, it remains less investigated how and whether the module-level designs can further increase the conversion efficiency. Herein, following the recent demonstration of a tellurium (Te)-free TE generator, an increase is demonstrated in the efficiency by reducing both the electrical and thermal energy losses through simply optimizing geometric factors of filling factor and leg-pair numbers. These module-level optimizations enable a record conversion efficiency of 8.2% under a ∆T ≈ 260 K, thus fulfilling 90% of the theoretical efficiency of the materials and solidly exceeding the Bi2Te3 modules. Furthermore, module robustness against > 10 160 thermal cycles while preserving a relative efficiency of 95% is demonstrated. These findings highlight the importance of the optimization strategy at the module level and demonstrate the feasibility of using Te-free thermoelectric compounds to harvest the omnipresent low-grade heat.
CRIS-Team Scopus Importer:2023-03-20
Keywords: efficiency; module optimization; tellurium-free thermoelectrics; thermal cycling